The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12891-021-04027-9
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of an accelerometer-based navigation system in bilateral one-stage total knee arthroplasty

Abstract: Background Bilateral one-stage total knee arthroplasty (BTKA) have increased because it provides a number of advantages. Recently, Accelerometer-based navigation (ABN) system which guide the cutting plane without intramedullary disturbance might result in less endothelial and microvascular damage. Therefore, we hypothesized that the ABN may reduce blood loss, reduce postoperative pain, and better restore BTKA alignment compared to conventional instruments. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A retrospective case-control study by Jhurani, et al, found that patients who underwent SBTKA with computer navigation experienced no blood loss or blood transfusion bene t compared to those who underwent conventional SBTKA [32]. Similarly, a retrospective study by Laoruengthana, et al reported that ABN could not reduce blood loss or postoperative pain compared to conventional SBTKA [33]. A prospective randomized study by Song, et al reported that robotic-assisted TKA had signi cantly less postoperative mean drainage blood loss compared to conventional TKA among patients undergoing SBTKA [26].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective case-control study by Jhurani, et al, found that patients who underwent SBTKA with computer navigation experienced no blood loss or blood transfusion bene t compared to those who underwent conventional SBTKA [32]. Similarly, a retrospective study by Laoruengthana, et al reported that ABN could not reduce blood loss or postoperative pain compared to conventional SBTKA [33]. A prospective randomized study by Song, et al reported that robotic-assisted TKA had signi cantly less postoperative mean drainage blood loss compared to conventional TKA among patients undergoing SBTKA [26].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective case-control study by Jhurani et al found that patients who underwent SBTKA with computer navigation experienced no blood loss or blood transfusion benefit compared to those who underwent conventional SBTKA [ 35 ]. Similarly, a retrospective study by Laoruengthana et al reported that ABN could not reduce blood loss or postoperative pain compared to conventional SBTKA [ 36 ]. A prospective randomized study by Song et al reported that robotic-assisted TKA had significantly less postoperative mean drainage blood loss compared to conventional TKA among patients undergoing SBTKA [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…After a few simple registration steps, this device determines the lower limb alignment and suggests the resection plane in both the coronal and sagittal views with the capability of verifying or adjusting the resected surface as necessary. 11 12) Therefore, the ABN avoids the need for costly preoperative planning, does not require a bulky computer console and an infrared camera, precludes line-of-sight issues, and eliminates risks associated with the tracking pins. In addition, evidence demonstrated that the ABN is as accurate as the CAS, 13) and the learning curve for the ABN (5–7 cases required) is shorter than that for the CAS (20–30 cases required).…”
mentioning
confidence: 99%